Spectral analysis of heart rate variability in bronchial asthma. - Garrard, C; Seidler, A; McKibben, A; McAlpine, L; Gordon, D (1992)
Sympathetic and parasympathetic activity was evaluated in ten healthy controls, nine asymptomatic, untreated asthmatic subjects and ten asthmatic patients during treatment for acute asthma, by measurement of the variation in resting heart rate using frequency spectrum analysis. Heart rate was recorded by ECG and respiratory rate by impedance plethysmography. Spectral density of the beat-to-beat heart rate was measured within the low frequency band 0.04 to 0.10 Hz (low frequency power) modulated by sympathetic and parasympathetic activity, and within a 0.12 Hz band width at the respiratory frequency mode (respiratory frequency power) modulated by parasympathetic activity. Acute asthmatics had higher heart rates than either of the other two groups; this was probably related to the effects of beta-adrenoceptor agonist medication. Sympathetically mediated heart rate variability (normalized low frequency power) was significantly lower in both asymptomatic (p less than 0.002) and acute (p less than 0.02) asthma subjects compared to controls. This is consistent with altered sympathetic/parasympathetic regulation of heart rate in subjects with bronchial asthma.